1971
DOI: 10.2337/diab.20.9.586
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gestational Age, Birth and Feeding on the Insulinogenic Response to Glucose and Tolbutamide by Fetal and Newborn Rat Pancreas

Abstract: Perinatal maturation of the pancreatic beta cells was studied in the rat. Insulin synthesis proceeded rapidly between the twentieth gestational day and the third postnatal day. The insulin concentration in the pancreas and the amount of insulin available per gram of body weight reached a maximum sixty hours after birth and then decreased slowly toward the values observed in the adult rat. The pancreatic beta cells became responsive to glucose and to tolbutamide during the twenty-third day after fertilization. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
25
1

Year Published

1975
1975
1994
1994

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 9 publications
3
25
1
Order By: Relevance
“…The relatively high rate of biosynthesis, accompanied by a relatively low pancreatic insulin content and by relatively high levels of circulating hormone, characteristic of the rat fetus, are consistent with the observations of other workers (5,13,63) and suggest that the insulin turnover is faster in the fetus than in the suckling animal. On the other hand, if one calculates the ratio of the amount of insulin secreted by pancreatic islets isolated from animals of different ages and incubated in buffer containing glucose at concentrations of 30 and 300 mgjlOO ml, one observes (Table 1) a rather symmetrical developmental pattern which indicates that relatively more insulin is secreted at low glucose concentration at an age when glucose tolerance is impaired.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The relatively high rate of biosynthesis, accompanied by a relatively low pancreatic insulin content and by relatively high levels of circulating hormone, characteristic of the rat fetus, are consistent with the observations of other workers (5,13,63) and suggest that the insulin turnover is faster in the fetus than in the suckling animal. On the other hand, if one calculates the ratio of the amount of insulin secreted by pancreatic islets isolated from animals of different ages and incubated in buffer containing glucose at concentrations of 30 and 300 mgjlOO ml, one observes (Table 1) a rather symmetrical developmental pattern which indicates that relatively more insulin is secreted at low glucose concentration at an age when glucose tolerance is impaired.…”
Section: Discussionsupporting
confidence: 90%
“…However, the precise time at which the insulin-releasing mechanism begins to function has not been determined and may vary with the nature of the stimulus. Thus, the fetal pancreas, even though insensitive to glucose (4, SO), may respond to other substances (see Reference 37) so that, toward the end of pregnancy, the fetal serum insulin (IRI) reaches values that are higher than those found in the dam (2,13,26,42,63). A significant decrease in fetal serum IRI occurs on the last day of intrauterine life (14), at the time when the level of glucagon and, consequently, the glucagon to insulin ratio, increase markedly (14, 15, 3 l ) , possibly explaining why the mammalian neonate does not tolerate a glucose load as well as the adult animal (49,64).…”
mentioning
confidence: 99%
“…explants (7), pancreatic pieces (8,9), or isolated fetal (10) or neonatal (11) islets had been used supported the conclusion that glucose was not an insulinogenic agent before term. Other experiments suggested that the fetal B cells were not entirely glucose blind because phosphodiesterase inhibitors unmasked (10) or markedly enhanced (12) the secretagogue effect of glucose, and glucose alone was found capable of stimulating insulin biosynthesis (13).…”
Section: Methodsmentioning
confidence: 91%
“…This is of great physiological interest since in the 3-day-old rat pancreas regulation of insulin biosynthesis and release occurs in a period of islet and beta cell growth (54) and functional differentiation. Indeed, insulin content on the 3rd (55) day after birth rises to twice the insulin content of the 1st day of life (55). In this respect two points are noteworthy.…”
mentioning
confidence: 87%